Estudo químico-quântico da estabilidade das N-alquil nitrosaminas neutras e protonadas - Andrade, Railton Barbosa de (2016)
In this work we performed ωB97XD, CAM-B3LYP, CASSCF, MR-CISD, MRCISD+ Q and NEVPT2 calculations. The basis sets aug-cc-pVDZ and cc-pVTZ were used to assess the stability of certain neutral and protonated N-nitrosamines in the ground and excited states. In addition, we analyzed the effect of methylation on proton transfer. The initial proposal was to characterize the stationary points and the potential energy curves in the ground and excited state, in order to suggest a strategy that results in lower computational demand to be applied in larger systems (cyclic and bicyclic N-nitrosamines). The results indicate that the methodology MR-CISD/cc-pVTZ//MR-CISD/aug-cc-pVDZ may be appropriate to study the N-nitrosamines. The used functionals provided good descriptions to vertical excitation energy, but were not capable to represent the states correctly to dissociation curves. MR-CID+Q/cc-pVTZ results for the system (CH3)2NNO protonated indicate that protonation is more favorable for NDMA_1A, increasing energy in 17.5 kcal mol-1, and that the methylation significantly alter the intramolecular proton transfer barriers. With the aim to find a methodology with lower computational cost, use a reference wave function CASSCF (12, 9) at the level NEVPT2/cc-pVTZ was used study the neutral NDMA and results were consistent with both the theoretical and experimental parameters in the literature. For studies involving larger systems, for example, cyclic and bicyclic N-nitrosamines, NEVPT2 may be used, since it is completely paralyzed, and involves the use of a CASSCF larger than CAS (14, 10), which is a fundamental characteristic to study larger systems.